Performan Pertumbuhan dan Daya Cerna pada Ayam Kampung dengan Penggunaan Jenis Bahan Pakan yang Berbeda - Kaharuddin Kaharuddin; Hafsah Hafsah; Ummiani Hatta (Universitas Tadulako, 2020)
This study aims to determine the growth performance and digestibility of nutrients local chicken and super local chicken using different types of feed. The study was conducted in a Kawatuna Village, Mantikulore Subdistrict, Palu City, on January 13 - April 21, 2019. The study was designed using a Completely Randomized Design wira factorial patterns. The first factor is the type of chicken, namely local chicken and super local chicken, the second factor is the type of feed, which consists of commercial feed (P1), local feed (P2) and functional feed (P3). The study used 180 chickens consisting of 90 local chickens and 90 super local chickens . The variables observed were performance of growth and digestibility. Growth performance consisted of ration consumption, body weight gain, and ration conversied. Digestion consists of digestibility of crude protein and crude fat. The results showed that the interactied between chicken species and feed type had no significant effect (P> 0.05) on the growth performance (feed consumption, body weight gain and feed conversion) and digestibility. (protein and fat). The factor of chicken type had no significant effect (P> 0.05) on growth performances and protein digestibility, but had a very significant effect (P <0.01) on fat digestibility. The type of feed had a significant effect (P <0.05) on feed consumption, body weight gain, feed conversion and crude protein digestibility. The conclusions from the results of the study that growth performance (consumption, weight gain, feed conversion) and nutrient digestibilityies (crude protein and crude fat) were not significantly affected by interactions between types of chickens with feed types. Chicken species did not significantly affect the growth performance and protein digestibility, but fat digestibility differed significantly between local chicken (42.53%) and super local chicken (33.53%). The type of feed significantly affects growth performance and protein digestibilitis. But it is not significant in fat digestibility. The highest protein digestibility was found in the treatment of P3 (88.67%) and the highest fat digestibility, that is in the treatment of factory feed (P1) of (40.71%).